PERSPEKTIF GENDER PADA MASYARAKAT KOTA BANDA ACEH - Cahayu Astina (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2019)
This study aims to find out the perspective of the people in Banda Aceh regarding gender relations and to find out how the implementation of gender relations in the household life of the community in Banda Aceh City. The theory that forms the basis of this research is Bourdieu's theory which views power in the context of the theory of society, where he sees power as a culture and artificial symbolism which is continually legitimized through agent interaction and structure. The main way this happens is through what is called "habistus" or socialized norms or tendencies to guide behavior and thinking. This research was conducted through a qualitative approach with data collection techniques carried out by observation and interviews. The results of this study are gender perspectives on the people of Banda Aceh City, especially those who are considered to have higher education (Strata one and two) can be well understood. even though it turns out that there are still those who place the freedom of role for women to choose their desire to work outside the home or become fully housewives without increasing the purpose of freedom of work for women to become the second backbone in household finance. Helping wives to complete domestic work is not a taboo thing for them, but for some they still have an understanding that domestic work is entirely the responsibility of a wife.